Is there a universal drug for epilepsy? - S. G. Burd; A. V. Lebedeva; Yu. V. Rubleva; M. B. Mironov; T. M. Krasilshikova (Эпилепсия и пароксизмальные состояния, 2018)
The article reviews the use of antiepileptic drugs in various forms of epilepsy. We present a complex case of juvenile myoclonic epilepsy, the diagnostic process and antiepileptic therapy. Our own data and the results of others demonstrated a high efficacy and tolerability of valproate drugs, and a low aggravation potential in all types of epileptic seizures.